2020
DOI: 10.1080/21642850.2020.1852939
|View full text |Cite
|
Sign up to set email alerts
|

Sleep attitudes as a predictor of sleep outcomes: a secondary data analysis

Abstract: Objectives Attitudes have been widely studied as predictors of a number of social and health behaviors. However, attitudes predicting sleep outcomes have only recently been examined, despite sleep being conceptualized as an important health behavior. Prior research has demonstrated that attitudes toward sleep are associated with sleep hygiene, sleep duration and quality (Peach & Gaultney, 2017 ; Peach, Gaultney, Ruggiero, 2018 ). Sleep attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Gender differences in sleep behavior indicate that gender can affect one's sleep behavior. Sleep behavior can indirectly predict the quality of one's sleep (Ruggiero et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gender differences in sleep behavior indicate that gender can affect one's sleep behavior. Sleep behavior can indirectly predict the quality of one's sleep (Ruggiero et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent work has reported sleep attitudes to successfully predict sleep hygiene, and sleep outcomes indirectly via sleep hygiene (A. Ruggiero et al, 2020). Sleep attitudes refer to one's perception of the value and utility of sleep, as well as their preference for sleeping over engaging in other activities (Peach & Gaultney, 2017).…”
Section: Public Interest Statementmentioning
confidence: 99%
“…Sleep attitudes can indirectly predict sleep outcomes through sleep hygiene practices (A. Ruggiero et al, 2020). Recent findings suggest that demographic variables, such as age, gender, race, and socioeconomic status (SES), likely moderate the relationship between sleep attitudes and sleep hygiene, thus affecting the indirect pathway (A.…”
Section: Public Interest Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Women also have better objective sleep quality, sleep duration, and sleep efficiency than men; however, they report poor sleep [41]. One study reported that subjective sleep quality was low in women [42]. In Australia, men stated that they think that their quality of sleep is better than that of women [43], and a report in China based on a Pittsburgh Sleep Quality Index (PSQI) survey suggested that women have worse quality of sleep than men [44].…”
Section: Introductionmentioning
confidence: 99%